Studies of Sport and Health Education Teachers in the University of Latvia in the Opinion of Graduates - Ābeļkalns, Ilvis; Golubeva, Ausma; Klempere - Sipjagina, Agita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article discusses the viewpoints of graduates of the program Health and sports teacher (Sports teacher – since 2011) in University of Latvia, Faculty of Pedagogy, Psychology and Art, on the particular study program, focusing on the importance of the educational environment. Parallel to the studies, students have the opportunity to develop their social experience, to participate in creative activities and to orientate themselves on a well-considered model of personal career. This article summarizes the opinions of the graduates on the study process and its importance as they commenced their professional activities, as well as opinions on the possibilities to engage in social and sports activities and the development of their careers in sports during the studies.